Surface orbital order and chemical potential inhomogeneity of the iron-based superconductor FeTe_{0.55}Se_{0.45} investigated with special STM tips - Dongfei Wang; Ruidan Zhong; Genda Gu; Roland Wiesendanger (Physical Review Research, 2021)
The atomically clean surface of the iron-based superconductor FeTe_{0.55}Se_{0.45} is investigated by low-temperature scanning tunneling microscope (STM) with different tip apex states. We show that the scattering channel between the Γ and X/Y points of the sample's Brillouin zone can be visualized clearly by a supersharp STM tip. Furthermore, by manipulating a single Fe atom onto the tip apex, signatures of the orbital nature of the subsurface Fe layer of FeTe_{0.55}Se_{0.45} can be identified. By preparing a charged tip state, the intrinsic spatial inhomogeneity of the chemical potential of FeTe_{0.55}Se_{0.45} can be revealed. As a result, three different types of vortex bound states originating from locally varying topological properties of the FeTe_{0.55}Se_{0.45} surface are observed by scanning tunneling spectroscopy.